The Effect of Service and Product Quality on Customer Satisfaction of Teh Tarik Jodi Manahan - Nabila Rahmawati; Muhammad Syihabuddin (Jurnal Multidisiplin Sahombu, 2026)
The growth of the culinary industry in Indonesia, particularly the trendy beverage segment, requires businesses to not only present attractive products but also provide satisfactory service to customers. Teh Tarik Jodi Manahan, a beverage shop in Surakarta City, faces challenges in maintaining customer satisfaction, despite its product flavors that are popular with young consumers. This study aims to analyze the influence of service quality and product quality on customer satisfaction, both partially and simultaneously. The study used a quantitative approach with a causal associative method. The study population was all Teh Tarik Jodi Manahan customers, with a sample of 83 respondents selected through purposive sampling. Data were collected using a 1–5 Likert scale questionnaire and direct observation of service and product conditions. Data analysis was performed using multiple linear regression using SPSS version 26, supplemented by validity, reliability, and classical assumption tests. The results showed that service quality and product quality simultaneously had a positive and significant effect on customer satisfaction. Partially, both variables also showed a positive effect on satisfaction, with the largest contribution coming from service quality. This study implies that improving service quality and product quality consistency are important strategies for maintaining customer loyalty and increasing customer satisfaction in the trendy beverage industry.